Are concentrations of pollutants in sharks, rays and skates (Elasmobranchii) a cause for concern? A systematic review. (November 2020) - Tiktak, Guuske P.; Butcher, Demi; Lawrence, Peter J.; Norrey, John; Bradley, Lee; Shaw, Kirsty; Preziosi, Richard; Megson, David
Abstract: This review represents a comprehensive analysis on pollutants in elasmobranchs including meta-analysis on the most studied pollutants: mercury, cadmium, PCBs and DDTs, in muscle and liver tissue. Elasmobranchs are particularly vulnerable to pollutant exposure which may pose a risk to the organism as well as humans that consume elasmobranch products. The highest concentrations of pollutants were found in sharks occupying top trophic levels (Carcharhiniformes and Lamniformes). A human health risk assessment identified that children and adults consuming shark once a week are exposed to over three times more mercury than is recommended by the US EPA. This poses a risk to local fishing communities and international consumers of shark-based products, as well as those subject to the widespread mislabelling of elasmobranch products. Wider screening studies are recommended to determine the risk to elasmobranchs from emerging pollutants and more robust studies are recommended to assess the risks to human health. Highlights: This review identified 176 papers on pollutant exposure in elasmobranchs. High concentrations of Hg, DDT and PCBs pose a serious threat to elasmobranchs. Humans are at risk of exposure to pollutants through consumption of elasmobranchs. Hg and DL-PCB concentrations in sharks are above human safety consumption limits. Research is required on emerging pollutants and in several key understudied regions.